ANALYSIS OF THE HARMONIC LOSSES WITH ARTIFICIAL NEURAL NETWORKS IN UNBALANCED SYSTEM LOSSES USING BALANCED ELECTRIC POWER SYSTEM DATA - Inan, Aslan; Koroglu, Selim; Izgi, Ercan (PAMUKKALE UNIV, 2005)
The losses in the power systems should be low as possible as. Saving energy instead of loses (kWh) in power utilities can supply much more energy to the consumers. The lower losses the more energy is saved and thus the power system becomes more economical. In recent years, the increasing number of applications and power ratings of the devices which have nonlinear voltage-current characteristics cause voltage waveform distortion and additional losses. While evaluating losses considering harmonics will provide more contribution to obtain more accurate results. In this study, Artificial Neural Networks (ANN) method has been presented to predict the harmonic losses in unbalanced power systems by using the data from balanced power system with nonlinear loads.
Keywords: Harmonic losses; Artificial neural networks; Nonlinear loads; Unbalanced loading; Engineering